ISSUES OF IMPROVING THE EFFICIENCY OF CORPORATE GOVERNANCE IN ENTERPRISES IN THE CONTEXT OF MODERNIZATION OF THE ECONOMY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the formation, development and improvement of corporate governance in Uzbekistan. The conditions for the organization of effective functioning of corporate governance mechanisms are analyzed.